The Impact of the Construction of the Haekrit Dam on the Social and Economic Life of the Farming Community in Manleten Village, East Tasifeto District - Pareira, Theofelo H Do Santos; Fransina W Balo; Maria Indriyani Hewe Tiwu (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research aims to explain the impact of the construction of the Haekrit Dam on the economic and social life of farming communities in Manleten Village, East Tasifeto District. This research use desciptive qualitative approach. Data collection used was interviews, observation and documentation. The analysis was carried out in several stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this research show that the impact of the construction of the dam on the social life of farming communities still often causes social conflict between farmers regarding the use of irrigation, but land acquisition does not have a negative effect, while the construction of the Haekrit Dam has a positive effect on the economic life of farming communities such as there are changes and additions to livelihoods, increasing the income of farming communities